Charge Transport in C60-based Single-Molecule Junctions with Graphene Electrodes - Leitherer, Susanne; Brana Coto, Pedro; Ullmann, Konrad; Weber, Heiko B.; Thoss, Michael (Nanoscale, 2017)
We investigate charge transport in C60-based single-molecule junctions with graphene electrodes employing a combination of density functional theory (DFT) electronic structure calculations and Landauer transport theory. In particular, the dependence of the transport properties on the conformation of the molecular bridge and the type of termination of the graphene electrodes is investigated. Furthermore, electron pathways through the junctions are analyzed using the theory of local currents. The results reveal, in agreement with previous experiments, a pronounced dependence of the transport properties on the bias polarity, which is rationalized in terms of the electronic structure of the molecule. It is also shown that the edge states of zigzag-terminated graphene induce additional transport channels, which dominate transport at low voltages. The importance of the edge states for transport depends profoundly on the interface geometry of the junctions.

Electron dynamics in graphene reaching the light-field-driven regime - Higuchi, Takuya; Heide, Christian; Ullmann, Konrad; Weber, Heiko B.; Hommelhoff, Peter (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2022-04-14

Gateless patterning of epitaxial graphene by local intercalation - Sorger, Christian; Hertel, Stefan; Jobst, Johannes; Steiner, Christian; Meil, Katharina; Ullmann, Konrad; Albert, A.; Wang, Yabin; Krieger, Michael; Ristein, Jürgen; Maier, Sabine; Weber, Heiko B. (Nanotechnology, 2015)
We present a technique to pattern the charge density of a large-area epitaxial graphene sheet locally without using metallic gates. Instead, local intercalation of the graphene-substrate interface can selectively be established in the vicinity of graphene edges or prede fined voids. It provides changes of the work function of several hundred meV, corresponding to a conversion from n-type to p-type charge carriers. This assignment is supported by photoelectron spectroscopy, scanning tunneling microscopy, scanning electron microscopy and Hall effect measurements. The technique introduces materials contrast to a graphene sheet in a variety of geometries and thus allows for novel experiments and novel functionalities.
UnivIS-Import:2015-04-14:Pub.2015.nat.dphy.IAP.LAP.gatele
Keywords: Graphene; Intercalation; Patterning

Landau-Zener-Stückelberg interferometer on attosecond timescales in graphene - Higuchi, Takuya; Heide, Christian; Ullmann, Konrad; Weber, Heiko B.; Hommelhoff, Peter (Proceedings of SPIE - The International Society for Optical Engineering, 2018)
When solids are exposed to intense optical fields, the intraband electron motion may influence interband transitions, potentially causing a transition of light-matter interaction from a quantum (photon-driven) regime to a semi-classical (field-driven) regime. We demonstrate this transition in monolayer graphene. We observe a carrier-envelope-phasedependent current in graphene irradiated with phase-stable two-cycle laser pulses, showing a striking reversal of the current direction as a function of the driving field amplitude at ∼2 V/nm. This reversal indicates the transition into the field-driven (or strong-field) regime. We show furthermore that in this regime electron dynamics are governed by suboptical-cycle Landau-Zener-Stückelberg interference, comprised of coherent repeated Landau-Zener transitions. We expect these results to have direct ramifications for light-wave driven electronics in graphene.
CRIS-Team Scopus Importer:2022-04-14
Keywords: attosecond physics; grapheme; light-field electronics; strong-field physics

Light-field driven currents in graphene - Higuchi, Takuya; Heide, Christian; Ullmann, Konrad; Weber, Heiko B.; Hommelhoff, Peter (arXiv, 2016)
Ultrafast electron dynamics in solids under strong optical fields has recently found particular attention. In dielectrics and semiconductors, various light-field-driven effects have been explored, such as high-harmonic generation, sub-optical-cycle interband population transfer and nonperturbative increase of transient polarizability. In contrast, much less is known about field-driven electron dynamics in metals because charge carriers screen an external electric field in ordinary metals. Here we show that atomically thin monolayer Graphene offers unique opportunities to study light-field-driven processes in a metal. With a comparably modest field strength of up to 0.3 V/Å, we drive combined interband and intraband electron dynamics, leading to a light-field-waveform controlled residual conduction current after the laser pulse is gone. We identify the underlying pivotal physical mechanism as electron quantum-path interference taking place on the 1-femtosecond (10-15s)timescale. The process can be categorized as Landau-Zener-St"uckelberg interferometry. These fully coherent electron dynamics in graphene take place on a hitherto unexplored timescale faster than electron-electron scattering (tens of femtoseconds) and electron-phonon scattering (hundreds of femtoseconds). These results broaden the scope of light-field control of electrons in solids to an entirely new and eminently important material class – metals – promising wide ramifications for band structure tomography and light-field-driven electronics.

Light-field-driven currents in graphene - Higuchi, Takuya; Heide, Christian; Ullmann, Konrad; Weber, Heiko B.; Hommelhoff, Peter (Nature, 2017)
The ability to steer electrons using the strong electromagnetic field of light has opened up the possibility of controlling electron dynamics on the sub-femtosecond (less than 10−15 seconds) timescale. In dielectrics and semiconductors, various light-field-driven effects have been explored, including high-harmonic generation1, 2, 3, 4, sub-optical-cycle interband population transfer5 and the non-perturbative change of the transient polarizability6, 7. In contrast, much less is known about light-field-driven electron dynamics in narrow-bandgap systems or in conductors, in which screening due to free carriers or light absorption hinders the application of strong optical fields6, 8. Graphene is a promising platform with which to achieve light-field-driven control of electrons in a conducting material, because of its broadband and ultrafast optical response, weak screening and high damage threshold9, 10. Here we show that a current induced in monolayer graphene by two-cycle laser pulses is sensitive to the electric-field waveform, that is, to the exact shape of the optical carrier field of the pulse, which is controlled by the carrier-envelope phase, with a precision on the attosecond (10−18 seconds) timescale. Such a current, dependent on the carrier-envelope phase, shows a striking reversal of the direction of the current as a function of the driving field amplitude at about two volts per nanometre. This reversal indicates a transition of light–matter interaction from the weak-field (photon-driven) regime to the strong-field (light-field-driven) regime, where the intraband dynamics influence interband transitions. We show that in this strong-field regime the electron dynamics are governed by sub-optical-cycle Landau–Zener–Stückelberg interference11, composed of coherent repeated Landau–Zener transitions on the femtosecond timescale. Furthermore, the influence of this sub-optical-cycle interference can be controlled with the laser polarization state. These coherent electron dynamics in graphene take place on a hitherto unexplored timescale, faster than electron–electron scattering (tens of femtoseconds) and electron–phonon scattering (hundreds of femtoseconds)12, 13, 14. We expect these results to have direct ramifications for band-structure tomography2 and light-field-driven petahertz electronics8</sup

Lightwave-controlled electron dynamics in graphene - Heide, Christian; Higuchi, Takuya; Ullmann, Konrad; Weber, Heiko B.; Hommelhoff, Peter (205, 2019)
We demonstrate that currents induced in graphene by ultrashort laser pulses are sensitive to the exact shape of the electric-field waveform. By increasing the field strength, we found a transition of the light–matter interaction from the weak-field to the strong-field regime at around 2 V/nm, where intraband dynamics influence interband transitions. In this strong-field regime, the light-matter interaction can be described by the wavenumber trajectories of electrons in the reciprocal space. For linearly polarized light the electron dynamics are governed by repeated sub-optical-cycle Landau-Zener transitions between the valence- and conduction band, resulting in Landau-Zener-Stuckelberg interference, whereas for circular polarized light this interference is supresse

Robust graphene membranes in a silicon carbide frame - Waldmann, Daniel; Butz, Benjamin; Bauer, Sebastian; Englert, Jan; Jobst, Johannes; Ullmann, Konrad; Fromm, Felix; Ammon, Maximilian Michael; Enzelberger-Heim, Michael; Hirsch, Andreas; Maier, Sabine; Schmuki, Patrik; et al. (ACS nano, 2013)
We present a fabrication process for freely suspended membranes consisting of bi- and trilayer graphene grown on silicon carbide. The procedure, involving photoelectrochemical etching, enables the simultaneous fabrication of hundreds of arbitrarily shaped membranes with an area up to 500 μm(2) and a yield of around 90%. Micro-Raman and atomic force microscopy measurements confirm that the graphene layer withstands the electrochemical etching and show that the membranes are virtually unstrained. The process delivers membranes with a cleanliness suited for high-resolution transmission electron microscopy (HRTEM) at atomic scale. The membrane, and its frame, is very robust with respect to thermal cycling above 1000 °C as well as harsh acidic or alkaline treatment.

Single-Molecule Junctions with Epitaxial Graphene Nanoelectrodes - Ullmann, Konrad; Brana Coto, Pedro; Leitherer, Susanne; Molina-Ontoria, Agustin; Martin, Nazario; Thoss, Michael; Weber, Heiko B. (Nano Letters, 2015)
On the way to ultraflat single-molecule junctions with transparent electrodes, we present a fabrication scheme based on epitaxial graphene nanoelectrodes. As a suitable molecule, we identified a molecular wire with fullerene anchor groups. With these two components, stable electrical characteristics could be recorded, Electrical measurements show that single-molecule junctions with graphene and with gold electrodes display a striking agreement. This motivated a hypothesis that the differential Conductance spectra are rather insensitive to the electrode material. It is further corroborated by the assignment of asymmetries and spectral features to internal molecular,degrees of freedom. The demonstrated open access graphene electrodes and the electrode-insensitive, molecules provide a model system that will allow for a thorough investigation of an individual single,molecule contact with additional probes.
Keywords: Epitaxial graphene nanoelectrodes; electroburning; single-molecule junctions; fullerene end groups; switching